The Acute Effects of Standing on Executive Functioning in Vocational Education and Training Students: The Phit2Learn Study - Luteijn, Petra J.; van der Wurff, Inge S. M.; Singh, Amika S.; Savelberg, Hans H. C. M.; de Groot, Renate H. M. (Frontiers in Psychology, 2022)
Research suggests that sedentary behavior (SB) is negatively associated with cognitive outcomes. Interrupting prolonged sitting has been shown to improve cognitive functions, including executive functioning (EF), which are important for academic performance. In this study we investigated the acute effects of reducing SB by short-time standing on EF in vocational education and training (VET) students. In a randomized crossover study, 165 VET students were first taught for 15 minutes in seated position. After this, they performed while seated the Letter Memory Test for updating, and the Color Shape Test for shifting and inhibition. Students were randomly assigned to a sitting or standing condition. All students were taught again for 15 minutes and then took the same tests in the condition they were allocated to, respectively standing or seated. After one week the test procedure was repeated, in which students switched conditions. Mixed model analyses showed no significant effect of sitting or standing on updating, B = .51, SEb = .50, 95%CI = [-.49, 1.51], shifting, B = -9.47, SEb = 15.05, 95%CI = [-39.30, 20.36], or inhibition, B = .70, SEb = 11.20, 95%CI = [-21.51, 22.90]. Also, no significant differences were found for the order of condition on updating, B = -.34, SEb = .60, 95%CI = [-1.54, .85], shifting, B = -9.57, SEb = 26.39, 95%CI = [-61.67, 42.54], or inhibition, B = 6.61, SEb = 14.28, 95%CI = [-21.61, 34.83]. Our results suggest that 40 minutes of standing does not significantly influence EF among VET students.